2014
DOI: 10.1186/1472-6955-13-4
|View full text |Cite
|
Sign up to set email alerts
|

Preventing falls among older people with mental health problems: a systematic review

Abstract: BackgroundFalls are a leading cause of mortality and morbidity in older people and the risk of falling is exacerbated by mental health conditions. Existing reviews have focused on people with dementia and cognitive impairment, but not those with other mental health conditions or in mental health settings. The objective of this review is to evaluate the effectiveness of fall prevention interventions for older people with mental health problems being cared for across all settings.MethodsA systematic review of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 54 publications
1
51
0
1
Order By: Relevance
“…7,8 These results show a high possibility of improvement of BPSD, although it is difficult to fundamentally improve core symptoms at the present moment, so it is important to focus on and respond individually to BPSD with the prevention of falls for older adults with dementia. 11,12 In contrast, in other studies about people with dementia falling, BPSD were assessed by a total score. 9,10 To prevent people with dementia from falling, it is important to clarify the relationships between falling and each problem as BPSD with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 These results show a high possibility of improvement of BPSD, although it is difficult to fundamentally improve core symptoms at the present moment, so it is important to focus on and respond individually to BPSD with the prevention of falls for older adults with dementia. 11,12 In contrast, in other studies about people with dementia falling, BPSD were assessed by a total score. 9,10 To prevent people with dementia from falling, it is important to clarify the relationships between falling and each problem as BPSD with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Preventative measures such as exercise, education and vitamin D supplements have been shown to have a non- or inconclusive effect in the residential care facility population (Avenell, Mak, & O’Connell, 2014; Bunn et al, 2014; Cameron et al, 2012). Although a review of complex multifactorial intervention programs has shown a reduction of recurrent fallers (Vlaeyen et al, 2015), there are considerable barriers for implementation outside the highly controlled circumstances of a study (Vlaeyen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence-based interventions have been developed, for example, through improvements in elderly care, training programmes for community dwelling elderly and home safety assessments 4. For elderly living in care facilities or with mental health problems, however, limited interventions have proven to be effective 5 6…”
Section: Introductionmentioning
confidence: 99%